Digital Readiness in Physical Education and Sports Health Learning: Study at Elementary School, Yogyakarta - Erwin Setyo Kriswanto; Firmansyah Firmansyah; Ranintya Meikahani; Dennis Dwi Kurniawan; Rizki Mulyawan (Jurnal Prima Edukasia, 2023)
Existing technological developments require all fields to be able to adjust to conditions in terms of technology. Several studies related to the use of technology during the COVID-19 pandemic in Indonesia show the unpreparedness of educators to adapt to emergency conditions that demand the use of online and hybrid learning, especially in PJOK subjects. Based on this, the researcher aims to determine the pattern of distance learning carried out by Physical Health and Sports Education teachers in elementary schools in Yogyakarta. Sequential explanatory design is used with quantitative and qualitative research approaches that are carried out sequentially. This research aims to analyze the need to develop learning media that can be used online, offline and in blended learning. The analysis of existing learning patterns shows that most teachers have met the standards of distance learning implementation. However, learning media development on certain materials still needs to be done to support each material delivery activity carried out by the teacher. The survey results show that most teachers still use teaching materials in print or electronic form and existing learning videos. The results of in-depth interviews indicate that there is still a need to develop learning media on athletic activities, self-defense, physical fitness development activities, gymnastics, rhythmic motion, water activities, personal safety, and a healthy lifestyle. With the results of this analysis, it is hoped that it can provide ideas and inspiration for further research in developing learning media, especially Physical Health and Sports Education in elementary schools so that educational goals towards the era of society 5.0 involve various technological developments can be achieved optimally both in emergency and normal conditions.